Distribution Of Lipids And Phosphatases In Adrenal Gland During Prenatal Development In Goat (Capra Hircus) (Applied Biological Research, 2015)
To elucidate the distribution of lipids, acid and alkaline phosphatase in  different parts of adrenal gland at various stages of gestation in goat the  present study was conducted on 24 healthy and normal foetii of non descript goat (Capra hircus) varying from day old to 150 days of  gestation at CVS&AH, Mathura (India) The foetii were assigned into  three groups according to their gestational ages: group I (0-50 days),  group II (51-100 days) and group III (101 days - till term). Capsule  showed traces to negative reaction in group-II but was devoid of lipids  in group-III. Cytoplasm of foetal cortical cells and definitive cortex  showed slight reaction for lipids but showed moderate reaction as the  age advanced. The cytoplasm of medullary cells was devoid of lipids.  Capsule showed moderate, whereas foetal cortex showed weak acid and  alkaline phosphatase reactions.
Keywords: Acid and alkaline phosphatase; adrenal; lipid; prenatal goat